Incidence de la pandémie de COVID-19 sur le bienêtre et la santé mentale des équipes1 de direction d’école : une recherche-action collaborative en milieux francophones minoritaires dans l’Ouest2 canadien - Rocque, Jules; Côté , Cynthia (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
This collaborative action research seeks to better understand the impact of COVID-19 on the well-being and mental health of school administrators (N = 63) in francophone settings in Western Canada. The results (obtained by a questionnaire and analysed with SPSS) show that even if these managers lack time, they remain engaged and feel satisfied with their work. Less than half claim to have a good work-life balance and almost 40% have difficulty sleeping at night. Participants with less experience in school administration seem to be hardest hit, and more than 75% of participants admit to having anxiety and numerous stress management strategies. This exploratory study underlines the importance of caring about the mental health and well-being of school administrators while considering additional resources to support them in their duties.